Research on Telecommunication System Business Security Architecture - Hong Li; Kai Qu (Dianxin kexue)
The concept of service security was thoroughly analyzed,and the generalized and narrow business security was proposed.The generalized business safety system was divided into five layers,and network security and safety requirements were defined,meanwhile the narrow business security was focused on the security of application layer,which was the concentration of the research.The security of application layer mainly includes two aspects:common vulnerabilities and loopholes in the service logic,which are defined and researched intensively.A security architecture against the security problem of the business-oriented system,and the security architecture taken as a better guideline for the design and implementation of business systems were proposed.